Financial Differences and Business Cycle Co-Movements in A Currency Area - Ester Faia (Oesterreichische Nationalbank (OeNB), 2005)
I propose a unitary framework to interpret the links between differences in financial structures and the monetary policy regimes on the one hand, and the correlation of business cycles on the other. Using a two-country micro-founded model with financial frictions I predict that a greater financial diversity should reduce cyclical correlation under a given monetary regime, and that moving from independent monetary policies to a hard peg or a common currency should increase it, for any given degree of financial diversity. I use the recent experience of EMU to test these ideas, and show that my model explains reasonably well the broad patterns of business cycle correlation observed recently among the main euro area countries.
Keywords: E3; E42; E44; E52; F41; 330; financial diversity; monetary regimes; differential transmission mechanism